Is It Impossible for Generation Z to Engage in Mindful Consumption Behaviour while Experiencing FOMO? - Alfina, Alfina; Khoirina, Marisya Mahdia; Sisprasojo, Nova Ridho; Ratri, Angela Ayu Kusumaning (Journal The Winners, 2024)
FOMO is often employed as an effective marketing strategy to increase excessive consumption behavior among Generation Z. However, over-reliance on FOMO strategies poses a threat to marketers, as excessive exposure to information on social media can lead to social media fatigue, which may hinder the development of mindful consumption behaviour. The research aimed to examine the relationship between fear of missing out (FOMO), social media fatigue (SMF), mindfulness, and mindful consumption behaviour (MCB) in Generation Z. The research applied an empirical approach through quantitative analysis. The proposed theoretical model was empirically tested using primary data collected by a self-designed structured questionnaire. The research sample comprised individuals aged between 13 and 25, as this demographic is the most active user on social media. The model was empirically tested using structural equation modelling applied through partial least squares (PLS) software. The findings reveals the significance of FOMO in influencing social media fatigue, mindfulness, and mindful consumption behaviour in Generation Z. FOMO is confirmed as a predictor of consumption behavior, specifically mindful consumption behavior. Also, FOMO is found to have a significant correlation with social media fatigue, which is due to the excessive exposure to various information on social media by Generation Z.